2020
DOI: 10.3233/jvr-201083
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of video-based interventions to improve integrated competitive employment skills among youth and adults with Autism Spectrum Disorder

Abstract: BACKGROUND: People with Autism Spectrum Disorder (ASD) have lower employment rates than their peers without disabilities or other disabilities. Clear evidence exists regarding video-based interventions (VBIs) for improving task performance and social communication skills for students with ASD. However, such interventions have rarely been applied in integrated employment settings. OBJECTIVE: This systematic literature review aims to examine the utilization and efficacy of video-based interventions in improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
(71 reference statements)
1
12
0
Order By: Relevance
“…In this study, a majority of student participants who had reported race information were White. This tendency was also captured in the review conducted by Munandar et al (2020). Considering the persistent racial disparities in employment (Winsor et al, 2021), it is critical to involve participants well representing different races in establishing evidence-based practice which will further contribute to the equality of vocational training and job opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a majority of student participants who had reported race information were White. This tendency was also captured in the review conducted by Munandar et al (2020). Considering the persistent racial disparities in employment (Winsor et al, 2021), it is critical to involve participants well representing different races in establishing evidence-based practice which will further contribute to the equality of vocational training and job opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…When VBI is used in employment settings, it can be effective in teaching vocational skills to autistic individuals, including both discrete skills, such as faxing or food preparation, and employment-related "soft skills" such as greeting customers or interacting with co-workers, as evident from multiple syntheses of the literature Munandar et al, 2020). Participants in some studies have also demonstrated maintenance of the vocational skills learned with VBI Munandar et al, 2020). Yet, despite this encouraging evidence, there remains a gap in the literature regarding the effective implementation of VBI in authentic settings (i.e., real workplace settings) by authentic agents (i.e., non-researchers).…”
Section: Video-based Intervention (Vbi) For Vocational Skillsmentioning
confidence: 99%
“…The SDLMI consists of three phases: setting a goal, taking action, and adjusting the goal or plan (Shogren et al., 2019). Video modeling can teach independence, social, and employability skills (e.g., Bross et al., 2020; Munandar et al., 2020; Park et al., 2020). A smartphone or tablet can record task completion and later provide skill maintenance (e.g., Khowaja et al., 2020; Muharib et al., 2021).…”
Section: Vertical Transition To Ecsementioning
confidence: 99%